If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 1) + 3(2x + 1) = 0 Reorder the terms: 4(1 + 2x) + 3(2x + 1) = 0 (1 * 4 + 2x * 4) + 3(2x + 1) = 0 (4 + 8x) + 3(2x + 1) = 0 Reorder the terms: 4 + 8x + 3(1 + 2x) = 0 4 + 8x + (1 * 3 + 2x * 3) = 0 4 + 8x + (3 + 6x) = 0 Reorder the terms: 4 + 3 + 8x + 6x = 0 Combine like terms: 4 + 3 = 7 7 + 8x + 6x = 0 Combine like terms: 8x + 6x = 14x 7 + 14x = 0 Solving 7 + 14x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 14x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 14x = 0 + -7 14x = 0 + -7 Combine like terms: 0 + -7 = -7 14x = -7 Divide each side by '14'. x = -0.5 Simplifying x = -0.5
| 2x^4-9x^2+9=0 | | 4a+1-a=8 | | (5+3x)(7-x)=0 | | 7x^2-18x+108=0 | | 6x+5=-x+19 | | 2sinx+cosx+1=0 | | (3x-7)(5-3x)=0 | | -88-2x+11x=101 | | 4x-5+3yi+4i=3+7i | | 2(c-3)=c+1 | | b+1=3b | | Ln(x)=0.480036 | | lnx=0.480036 | | 2x+3y=365 | | 2xg=15-3xg | | -13x^2+54x-60=0 | | 8x-18+x+18=90 | | -10x^2-3x+9=0 | | (x-3)*3=9 | | .8x=1.2 | | 12x-8x=162-43x | | 9x-66+x=94 | | 4+7x-4=5-2x+8x | | 2*x=15-3*x | | 4x^5+x-0.05=0 | | 9x^2+79=-18 | | 7x-6x-40=24 | | -23x^2+162x-180=0 | | 14=4x-18 | | 9000000+2000000x=5000000 | | 3x+14=7x-18 | | 4x^5+x-0.1=0 |